Potential of Pectins to Beneficially Modulate the Gut Microbiota Depends on Their Structural Properties - Larsen, Nadja; Bussolo de Souza, Carlota; Krych, Lukasz; Barbosa Cahú, Thiago; Wiese, Maria; Kot, Witold; Hansen, Karin Meyer; Blennow, Andreas; Venema, Koen; Jespersen, Lene (Frontiers in Microbiology, 2019)
Pectins are plant cell-wall polysaccharides which can be utilized by commensal bacteria in the gut, exhibiting beneficial properties for the host. Knowledge of the impact of pectins on intestinal bacterial communities is insufficient and limited to a few types of pectins. This study characterized the relationship between the structural properties of pectins and their potential to modulate composition and activity of the gut microbiota in a beneficial way. For this purpose we performed in vitro fermentations of nine structurally diverse pectins from citrus fruits and sugar beet, and a pectic derivative, rhamnogalacturonan I (RGI), using a TIM-2 colon model. The composition of microbiota during TIM-2 fermentations was assessed by 16S rRNA gene amplicon sequencing. Both general and pectin-specific changes were observed in relative abundances of numerous bacterial taxa in a time-dependent way. Bacterial populations associated with human health, such as Faecalibacterium prausnitzii, Coprococcus, Ruminococcus, Dorea, Blautia, Oscillospira, Sutterella, Bifidobacterium, Christensenellaceae, Prevotella copri, and Bacteroides spp. were either increased or decreased depending on the substrate, suggesting that these bacteria can be controlled using structurally different pectins. The main structural features linked to the pectin-mediated shifts in microbiota included degree of esterification, composition of neutral sugars, distribution of homogalacturonan and rhamnogalacturonan fractions, degree of branching and the presence of amide groups. Cumulative production of the total short chain fatty acids and propionate was largest in fermentations of the high methoxyl pectins. Thus, this study indicates that microbial communities in the gut can be specifically modulated by pectins and identifies the features in pectin molecules linked to microbial alterations. This knowledge can be used to define preferred dietary pectins, targeting beneficial bacteria and favoring more balanced microbiota communities in the gut.